1995
DOI: 10.1172/jci117634
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of calcitonin receptor mRNA expression by calcitonin during human osteoclast-like cell differentiation.

Abstract: Calcitonin inhibits both osteoclast formation and bone resorption, and is a primary treatment for patients with hypercalcemia and increased bone turnover. However, the clinical utility of calcitonin is limited because patients become refractory to calcitonin after several days (the calcitonin "escape phenomenon"). The molecular basis for calcitonin "escape" is unclear. To determine the regulatory mechanisms controlling calcitonin receptor (CTR) expression in osteoclasts and their precursors, we treated immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(41 citation statements)
references
References 42 publications
2
34
0
5
Order By: Relevance
“…34 Calcitonin was also used for pain relief. Elcatonin has been used for many years to treat osteoporosis and osteoporotic fractures as it provides excellent pain relief, suppresses the activity of osteoclasts and increases bone density.…”
Section: H Tang J Zhao C Hao Management Of Osteoporotic Vertebral Cmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Calcitonin was also used for pain relief. Elcatonin has been used for many years to treat osteoporosis and osteoporotic fractures as it provides excellent pain relief, suppresses the activity of osteoclasts and increases bone density.…”
Section: H Tang J Zhao C Hao Management Of Osteoporotic Vertebral Cmentioning
confidence: 99%
“…35 − 37 There are, however, some disadvantages of using elcatonin in clinical applications. Longterm usage may lead to escape phenomenon 34 H Tang, J Zhao, C Hao Management of osteoporotic vertebral compression fractures morphology, thereby losing its role in bone resorption. Calcitonin does not relieve pain immediately, so another analgesic may be needed in the acute phase following fracture.…”
Section: H Tang J Zhao C Hao Management Of Osteoporotic Vertebral Cmentioning
confidence: 99%
“…Continuous treatment with calcitonin eventually leads to decreased inhibitory effects on osteoclastic bone resorption (escape phenomenon). This escape phenomenon is known to involve downregulation of the calcitonin receptor, which is derived from activation of the PKA pathway (17,18). Compounds that exert calcitonin-like activity without affecting the PKA pathway would be viewed as new types of antiresorptive agents.…”
Section: Disruptive Activity Of Destruxins On Actin Rings In Osteoclastsmentioning
confidence: 99%
“…It has been shown that the accumulation of calcitonin in the Golgi apparatus of osteoclasts is related to the down-regulation of CTR (Ikegame et al 1994). It has also been demonstrated that the synthesis of CTR is suppressed at the transcription level when osteoclast-like multinucleated cells (MNCs) are treated with calcitonin (Takahashi et al 1995, Findlay & Martin 1997. Such prolonged down-regulation of the CTR appears to be an important molecular aspect of the escape phenomenon.…”
Section: Introductionmentioning
confidence: 99%